CEO/CFO characteristics and ?nancial reporting quality: A review - Habib, A.; Hossain, Mahmud (J A I Press Inc., 2012)
This study reviews the literature on the association between different facets of CEO/CFO characteristics and the properties of accounting information. The review is organized around three broad themes, namely, the association between financial reporting quality and CEO/CFO turnover, the effect of managerial overconfidence on financial reporting outcomes, and finally the effect of CEO/CFO gender on reporting outcomes. This review illustrates the importance of considering CEO/CFO characteristics as an important determinant of financial reporting outcomes. This study offers insights to policy makers interested in enhancing the governance function to enhance the credibility of financial reporting. The review informs regulators that designing governance structure disregarding CEO/CFO characteristics may not bring desired benefits.